Hubungan Komunikasi Interpersonal Petugas Kesehatan Terhadap Kepatuhan Pasien Menjalani Pengobatan TB Paru di Puskesmas Sunggal Medan Tahun 2014 - Dermawanti Malau; R. Kintoko Rochadi; Tukiman . (Kebijakan, Promosi Kesehatan dan Biostatiskik, 2015)
Interpersonal communication is communication between two people face to face, which allows any other person reaction catch participants directly, either in verbal or nonverbal. Interpersonal communication is only consistedof two people, such us the patient and nurse, the husband and wife, teacher and student and etc. So that communicator can see the reaction given by komunikan. But the real practice interpersonal communication is often overlooked because of time belonging to the health worker. Treatment Compliance is a complete regularly and complete treatment without interrupted for at least 6 months up to 8 months. With good interpersonal communication built up between the health worker and the patients are expected to improve patient medication adherence.This research is descriptive analytic study with the purpose of analyzing the relations interpersonal communication health worker on the compliance of patients lived treatment of Pulmonary Tuberkulosis. The population in this study were all patients with Pulmonary Tuberculosis in Sunggal the Health Center and the number of samples is entire populations that as many as 42 people.Data was obtained with the interview using questionnaire were analyzed using Chi-square test at = 0.05. The results showed the frequency of adherent patients as many as 28 people (66,7%)and non-adherentmany as 14 people (33.3%). The results of statistical tests shows interpersonal communication variable aspects of openness, empathy, supportiveness and equality effect to compliance of patients lived treatment of pulmonary Tuberculosis in Medan Sunggal the Health Center. Pulmonary Tuberculosis.To the health worker advised that holds especially Pulmonary Tuberculosis program in order to always provide motivation to patients to regularly take medication at the health center.